2022
DOI: 10.2147/prbm.s372251
|View full text |Cite
|
Sign up to set email alerts
|

Burnout Among Saudi Radiological Sciences Undergraduate Students During COVID-19 Pandemic: A Cross-Sectional Study

Abstract: Background The novel Coronavirus Disease 2019 (COVID-19) pandemic has posed unprecedented new stressors and challenges to the applied health sciences’ education. This study explored the prevalence of burnout among Saudi radiological sciences students at King Saud bin Abdulaziz University for Health Sciences during the COVID-19 pandemic. Methods A cross-sectional study was conducted between November and December 2020 among 176-Saudi radiological sciences students, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…The study reported that burnout increased as students advanced to the fourth year. 21 Similarly, our findings revealed that 39% of the RADs students and interns felt stressed and overwhelmed during their study. The percentage increased to 47% during their clinical training, mainly during the fourth year of their study and the internship.…”
Section: Discussionsupporting
confidence: 61%
“…The study reported that burnout increased as students advanced to the fourth year. 21 Similarly, our findings revealed that 39% of the RADs students and interns felt stressed and overwhelmed during their study. The percentage increased to 47% during their clinical training, mainly during the fourth year of their study and the internship.…”
Section: Discussionsupporting
confidence: 61%
“…In comparison, an analysis of 19 studies involving 4108 healthcare professionals (women: 49.3%) conducted in Bahrain, Egypt, Jordan, Lebanon, Palestine, Saudi Arabia, and Yemen showed that there was a wide range of prevalence estimates in the MBI subscales, which revealed a low PA level (13.3). 19 Similar to the overall EE domain, there were no significant differences in PA according to sex, age, experience, or department (p<0.05). Many studies have found that younger age strongly predicted burnout.…”
Section: Discussionmentioning
confidence: 83%
“…17 Recent reviews have recommended the need for studies assessing the burnout level among a variety of healthcare providers, including laboratory scientists and radiographers. 18,19 A recent study found moderate to high burnout rates among Saudi radiological sciences students. It reported that academic counselling can help students cope with emotional stress and decrease the risk of burnout.…”
Section: Introductionmentioning
confidence: 99%
“…Although the COAMS programs follow traditional instructional methods, the curriculum also fosters an interactive and cooperative learning environment through the integration of diverse teaching strategies such as problem-based learning (PBL), small group discussions, and simulation to ensure achieving the learning outcomes. Challenges to remote interprofessional health education may include issues related to communication and barriers related to educational content and interaction between instructor and student, inadequacy for practical learning, student assessment, use of technology tools, online experience and inadequacy of internet and website services, pandemic-related anxiety or stress or burnout, time management, lack of motivation and technophobia ( 2 , 3 , 71 , 72 ). Besides the findings of our study, these challenges indicate the areas that require attention in interventions aimed at facilitating the successful implementation of interprofessional online education challenges, based on COAMS students’ perspectives in Saudi Arabia and elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, students have described how the pandemic has affected their social interactions, physical activity levels, overall stress levels, as well as how these alterations have changed their ability to remain productive ( 18 , 19 ). Another growing concern is the mental health of students, with stress, anxiety, and burnout being reported by university students during the COVID-19 pandemic ( 2 , 20 ).…”
Section: Introductionmentioning
confidence: 99%